FRI0129 Similarities and Differences between Axial and Peripheral Predominant Forms in Patients with Early Spondyloathritis: Results from the Esperanza Cohort. (10th June 2014) - del Río-Martínez, P.; Navarro-Compán, V.; Castillo-Gallego, C.; Castro, M.C.; Collantes-Estévez, E.; De Miguel, E.
Abstract : Background: Based on the predominant manifestation of the disease, the ASAS classification criteria for spondyloarthritis (SpA) distinguish two clinical forms: Axial SpA, including non-radiographic SpA and Ankylosing Spondylitis (AS), and peripheral SpA. Although both forms are considered as part of the same disease, published data are limited, especially in early disease. Objectives: To describe and compare the characteristics of patients fulfilling the ASAS criteria for axial SpA versus peripheral SpA in patients with recent symptoms onset. Methods: Baseline dataset from the early SpA ESPERANZA cohort was used. This cohort includes patients with the following referral criteria: Age <45 years, symptoms duration 3-24 months and with inflammatory back pain (IBP) or asymmetrical arthritis or spinal/joint pain plus ≥1 SpA features. A total of 377 patients fulfilling the ASAS classification criteria for SpA were included. Demographic and disease characteristics were compared between patients with axial SpA versus peripheral SpA. Results: Two hundred ninety one (77.2%) patients were classified as axial SpA (109 AS and 182 non-radiographic SpA) and 86 (22.8%) patients as peripheral SpA. Table shows the results (mean ± SD or relative frequency) for the comparison of demographic and disease characteristics between groups. Age, sex and disease activity scores were similar in both groups. However, axial SpA was more related to a delay in time to be referred to a specialist, uveitis and positive HLA-B27 while peripheral SpA was associated with enthesitis, psoriasis, dactylitis and inflammatory bowel disease (IBD). Conclusions: Early SpA patients with predominant axial symptoms are usually referred later to rheumatologists than patients with peripheral symptoms. However, the degree of disease activity is similar in both groups. Uveitis and HLA-B27 are more frequent in patients with predominant axial symptoms, while psoriasis, enthesitis, dactylitis and IBD are more frequent in patients with peripheral involvement. Acknowledgements: The EsPeranza Program has been supported by the Spanish Rheumatology Foundation and an unrestricted grant from Pfizer. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3260